Status Identification and Restoration Zoning of Ecological Space in Maowusu Sandy Land Based on Temporal and Spatial Characteristics of Land Use - Tiejun Zhang; Peng Xiao; Zhenqi Yang; Jianying Guo (Agronomy, 2025)
Maowusu sandy land is characterized by a fragile ecological environment and extreme sensitivity to external disturbances such as climate change and human activities. Identifying and zoning ecological spaces in this region are crucial for maintaining eco-environmental safety and promoting sustainable regional development. With Maowusu sandy land as the study object, the temporal and spatial characteristics of land use and the driving forces were explored via spatial analysis technology—the geographic information system. Then, a 2D relation judgment matrix was constructed by evaluating the importance of ecosystem service functions and ecological sensitivity. Next, restoration zoning of natural ecological space was performed, and relevant restoration suggestions were put forward accordingly. Results show that the land use in Maowusu sandy land has significantly changed in the past 30 years, with construction land and forest continuously expanding, cropland and grassland being squeezed, and some areas of unutilized land being transformed into other land use types. Ecosystem service functions tend to weaken from southwest to northeast, whereas the ecologically sensitive zones are mainly distributed in the middle of Maowusu sandy land. The high-importance and high-sensitivity zones of natural ecological space account for 3.60% of the total area of natural ecological space, mainly distributed near Ejin Horo Banner. A comprehensive restoration project of soil and water conservation should be conducted in this zone to alleviate soil erosion and maintain the management and restoration of ecological protection red lines. Moderately important sensitive zones account for the largest proportion (80.42%) of the total area of natural ecological space, being widely distributed. In such zones, water resources should be taken as constraints, with emphasis on ecological protection and improvement measures. Low-importance and low-sensitivity zones account for the smallest proportion, in which ecosystem protection, near-natural restoration, and moderate development and utilization should be carried out. This study aims to provide a scientific basis for reasonably protecting natural ecological resources and promoting the healthy and ordered development of natural ecosystems.